2005
DOI: 10.1124/jpet.105.090613
|View full text |Cite
|
Sign up to set email alerts
|

Shift from Biliary to Urinary Elimination of Acetaminophen-Glucuronide in Acetaminophen-Pretreated Rats

Abstract: Despite its toxicity, acetaminophen (APAP) is used increasingly as an analgesic, antipyretic, and anti-inflammatory agent. We examined the effect of prior exposure to APAP on its biliary and urinary elimination. The biliary and urinary elimination of a test dose of APAP (150 mg/kg i.v.) was determined in male Wistar rats 24 h after pretreatment with vehicle, a single dose (1.0 g/kg i.p.), or increasing daily doses (0.2, 0.3, 0.6, and 1.0 g/kg/day i.p.) of APAP. Although elimination of the parent APAP was minim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 36 publications
(62 reference statements)
3
46
0
Order By: Relevance
“…This hypothesis is supported by the fact that Kupffer cells participate not only in protecting the liver from APAP toxicity but also in upregulating hepatocellular Mrp4 protein (Campion et al, 2008). Work by Ghanem et al (2005) has provided an additional explanation for APAP autoprotection in rodents. Pretreatment of rats with increasing doses of APAP alters the excretion of the final high dose of APAP and corresponds to reduced hepatotoxicity (compared with rats receiving only the high dose).…”
Section: Klaassen and Aleksunessupporting
confidence: 54%
“…This hypothesis is supported by the fact that Kupffer cells participate not only in protecting the liver from APAP toxicity but also in upregulating hepatocellular Mrp4 protein (Campion et al, 2008). Work by Ghanem et al (2005) has provided an additional explanation for APAP autoprotection in rodents. Pretreatment of rats with increasing doses of APAP alters the excretion of the final high dose of APAP and corresponds to reduced hepatotoxicity (compared with rats receiving only the high dose).…”
Section: Klaassen and Aleksunessupporting
confidence: 54%
“…Western blot analyses of Mrp2, Bsep, and AE2 were performed in MPM as described . Detection of Mrp3 was performed also in MPM using a rabbit polyclonal antibody to rat Mrp3 (Ogawa et al, 2000), as previously described (Ghanem et al, 2005). Detection of UDP-glucuronosyltransferases (UGTs) was performed in microsomal preparations using polyclonal anti-peptide antibodies that specifically recognize the 1A6 and 1A7 isoforms belonging to UGT family 1 (Ikushiro et al, 1995), as previously reported (Luquita et al, 2001).…”
Section: Methodsmentioning
confidence: 99%
“…Liver viability was controlled throughout by monitoring LDH leakage into the perfusate (with values Ͻ10 IU/l between the start and the end of the experiment). The content of APAP-glu in bile, perfusate, and liver homogenate was determined by HPLC (Ghanem et al, 2005). UGT Activity.…”
Section: Spironolactone Prevents Ee-induced Cholestasismentioning
confidence: 99%
“…This finding was consistent with the observation that reduced biliary excretion was compensated to some extent by an increase in the renal clearance of CP-671,305 potentially due to adaptive changes in expression of other transporters in TR Ϫ rats. For example, it is known that the hepatic expression of Mrp3, which also mediates transport of organic anions across the hepatocyte basolateral membrane into sinusoidal blood, is significantly up-regulated in Mrp2-deficient rats (Hirohashi et al, 1998) and has been speculated to play a role in a compensatory shift from biliary to renal elimination for organic anions such as a acetaminophenglucuronide (Ghanem et al, 2005) and pravastatin (Kivistö et al, 2005). Whether CP-671,305 is a substrate for human and rat MRP3/ Mrp3 remains to be evaluated.…”
Section: Discussionmentioning
confidence: 99%